(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: The home can be the warmest and most caressing place in the world and can also be the scene of hell on earth. What kind of home a child was born in determines their entire life - and the life of their environment. All the love they can show during their life is what they once absorbed at home. Every drop of poison they have soaked up back there will flow out of them later. Therefore, curbing the phenomenon of domestic violence and making it unacceptable in the public eye has an overwhelming effect on the mental and criminal state of society as a whole. Between four walls, an adult can do anything at their own discretion, in their own home. But the freedom of an abuser is violating the liberty of the weaker family members. I write about domestic violence, homicide, and responses from the child protective services and the justice system. Methodology: For the past five years, I have been researching child abuse, relationship violence in connection with it, patricide, and infanticide through a comprehensive analysis of criminal records. Prior to examining the vast number of records, I dealt with juvenile delinquency for many years, a phenomenon that also led me back to the topic of domestic violence and neglect. Findings: Although there has been a lot of talk about domestic violence in recent years, complicit silence does not appear to be declining, and neither the child protective services’ nor the justice system’s responses are proving to be effective enough in curbing cases of domestic violence. Value: I hope the research results will help to recognize the real significance of the problem and improve its management. By keeping the topic alive and illustrating it, the goal is also to form public opinion.